Estimación anual de la emisión de CO2 asociada a la transportación de los docentes de la ULVR - Barzola, Julio (2014)
The carbon footprint is a sustainability indicator that measures the emissions of Greenhouse Gases (GHG). These emissions are attributable to a manufactured product, an organization or an individual; i.e. it directly or indirectly measures the impact or mark left on the environment by the emissions caused by man’s daily activities. This article estimates the GHG emissions produced by the population of teachers at Universidad Laica VICENTE ROCAFUERTE in Guayaquil for a year. For this purpose, a survey was applied to a significant sample with a 95% confidence level. Then with the information gathered, the estimations of the CO2 mass were made from two different approaches: Mass Conservation and Emission Factors. The results show a low percentage of error between both methods. Consequently, it is estimated that each teacher at ULVR produces 882.94 kg of CO2 or its equivalent during a year